The Nurses’ Mental Burden in Utilizing Electronic Medical Records in Hospitals - Husna, Eriana Mayasari; Purnami, Cahya Tri; Arso, Septo Pawelas (Newinera Publisher, 2025)
Electronic Medical Record (EMR) revolutionize patient information management in healthcare but pose challenges for nurses, who play a crucial role in their utilization. Despite perceived benefits, nurses face significant mental burdens navigating these systems, requiring tailored strategies for successful integration. This article explores nurses' challenges with EMRs and proposes solutions to alleviate their burden while ensuring efficient patient care. This study employed a systematic literature review following the PRISMA method. Conducting searches across databases Scopus and PubMed using keywords “electronic medical record” and “nurse”. Total of 22 selected articles show that Nurses' cognitive challenges with EMRs in hospitals stem from design complexities, impacting workflow and decision-making, exacerbated by factors like experience levels and external events like the COVID-19 pandemic, while usability, system quality, and participatory design approaches can mitigate stressors and enhance nurses' engagement and efficiency. Nurses' EMR experiences impact their well-being and patient care. Addressing these challenges requires optimizing design, usability, training, and support. Supporting nurses in EMR use enhances patient care and well-being, necessitating ongoing research and collaboration for improvement.